Research on Brain Based Learning Models in Biology Learning: A Systematic Literature Review - Azzahra, Waliyyatu; Diana, Sariwulan; Nuraeni, Eni; Haryanto, Haryanto (Bioeducation Journal, 2024)
Research on the application of the Brain-based Learning (BBL) Model in biology education has the potential to provide a deeper understanding of how the brain processes biological information. The aim of this study is to conduct a systematic literature review of previous studies on the application of the BBL Model in the context of biology education. A systematic literature review method was employed using the Scopus and Google Scholar databases as data sources. Out of the total articles found from 2013, a total of 17 articles met the established criteria and were then carefully analyzed. The analysis revealed several key findings, including (1) The trend of BBL research in biology education peaked in 2019; (2) The distribution of BBL research is still uneven in Indonesia, with the majority in the Java region; (3) Quantitative research methods dominate BBL research; (4) The implementation of BBL is widely relevant across various educational levels, but has not been applied to all levels; (5) The Classification System of Living Organisms is the most commonly chosen topic in BBL research; (6) The implementation of BBL has a positive impact on various aspects of student abilities. Based on these findings, BBL holds promise in supporting biology education. However, further research is needed to explore the BBL Model in a broader and more diverse context. Such research can delve deeper into various research methods, research subjects, and learning topics. Thus, more innovative and adaptive learning practices can be developed through a more comprehensive understanding of the potential of BBL in biology education.